The Effect Of Compensation On Employee Performance With Work Motivation As An Intervening Variable At The Dairi Regency Tourism, Culture, Youth And Sports Office - Syahyunan; Abdi Sugiarto (Yayasan Multidimensi Kreatif, 2025)
Providing appropriate compensation has an important role in improving employee motivation and performance in the work environment. This study aims to analyze the effect of compensation on employee performance through work motivation as an intervening variable at the Dairi Regency Tourism, Culture, Youth, and Sports Office. Using a causal associative quantitative method, this research was carried out at the Dairi Regency Tourism, Culture, Youth, and Sports Office with a total of 96 respondents. The results of the analysis show that compensation has a significant effect on work motivation and employee performance, as evidenced by the T-Statistic value of 27.267 > 1.96 and the P-Value of 0.000 < 0.05 for the effect of compensation on motivation. In addition, work motivation is also proven to have a significant influence on employee performance, with a T-Statistic value of 6.764 > 1.96 and a P-Value of 0.000 < 0.05. In Indirect Influence, it was obtained that motivation was able to intervene the influence between compensation and employee performance. This can be seen from the results of the T-Statistical value of 6.274 > 1.96 with a P-Value of 0.000 < 0.05. This shows that there is an indirect influence between compensation and employee performance through motivation. The implications of these results suggest that organizations, especially government agencies, need to consider compensation policies that include not only salaries and benefits but also other forms of compensation such as non-financial rewards to improve employee motivation and performance. An effective and adequate compensation policy, accompanied by a work environment that supports motivation, will create a synergistic effect that can increase employee productivity and loyalty.